T Lymphocytes in Patients With Nijmegen Breakage Syndrome Demonstrate Features of Exhaustion and Senescence in Flow Cytometric Evaluation of Maturation Pathway - Piatosa, Barbara; Wolska-Kuśnierz, Beata; Tkaczyk, Katarzyna; Heropolitanska-Pliszka, Edyta; Grycuk, Urszula; Wakulinska, Anna; Gregorek, Hanna (Frontiers in Immunology, 2020)
Patients with Nijmegen Breakage Syndrome (NBS) suffer from recurrent infections due to humoral and cellular immune deficiency. Despite low number of T lymphocytes and their maturation defect, the clinical manifestations of cell-mediated deficiency are not as severe as in case of patients with other types of combined immune deficiencies and similar T cell lymphopenia. In this study, multicolor flow cytometry was used for evaluation of peripheral T lymphocyte maturation according to the currently known differentiation pathway, in 46 patients with genetically confirmed NBS and 46 sex and age-matched controls. Evaluation of differential expression of CD27, CD31, CD45RA, CD95, and CD197 revealed existence of cell subsets so far not described in NBS patients. Although recent thymic emigrants and naïve T lymphocyte cell populations were significantly lower, the generation of antigen-primed T cells was similar or even greater in NBS patients than in healthy controls. Moreover, the senescent and exhausted T cell populations defined by expression of CD57, KLRG1, and PD1 were more numerous than in healthy people. Although this hypothesis needs further investigations, such properties might be related to an increased susceptibility to malignancy and milder clinical course than expected in view of T cell lymphopenia in patients with NBS.